Advanced materials for management of immune-related adverse events induced by immune checkpoint inhibitors. (July 2022) - Zheng, Lingnan; Yang, Xi; Wei, Yuanfeng; You, Jia; Li, Huawei; Liao, Jinfeng; Yi, Cheng
Graphical abstract: The role of emerging materials including nanoparticles, microneedles, hydrogels and cellular particulates in irAEs management. On one hand, therapeutic strategies based on materials science can prevent and alleviate irAEs as well as enhance anti-tumor efficacy by changing the delivery strategy of ICIs. On the other hand, advanced materials applied in immunosuppressive therapy can not only treat irAEs effectively without affecting the efficiency of ICB therapy, but also limit the additional side effects induced by immunosuppressive agents. Highlights: Although immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, they have also resulted in immune-related adverse events (irAEs). The precise mechanisms of irAEs induced by ICIs remain unknown and the management of irAEs remains a challenge. Recent developments in materials science have offered many promising strategies for effectively managing irAEs. Abstract: Immune checkpoint blockade (ICB) therapy has revolutionized the treatment of various types of cancer. However, even promising systemically administered ICB agents can cause immune-related adverse events (irAEs). The management of irAEs has been a significant concern. In addition to the risk of compromised immune function with corticosteroids and other immunomodulatory regimens used to treat irAEs, the complex mechanisms of irAEs make management of the "off-target" effects extremely challenging. Various materials with high biocompatibility, controllable degradability, and the ability for local and targeted delivery and controlled and sustained release of drugs have been explored to limit irAEs. Herein, we briefly review the fundamental mechanisms and clinical applications of immune checkpoint inhibitors and the potential mechanisms and clinical treatment of irAEs. We also highlight the application of emerging materials in the management of irAEs through "prevention" and "treatment".